Illegal occupation of state land in Perak: A review of the states legalisation program (PATUH) - Mohamed Osman, Mariana; Ab Wahab, Hanisah; Abdullah, Muhammad Faris; Mohamed, Mohd Zin (American Scientific Publishers, 2017)
Illegal occupation and operation of state land has negatively impacted the states in many ways, especially in terms of revenue loss and environmental pollution. To counter these impacts, states government have undertaken measures to curb illegal occupation and operation of state land. This study reviewed PATUH, a programme undertaken by the State Government of Perak to curb illegal occupation of government land in the state. Information regarding PATUH was obtained through interviews with officers from key government agencies in Perak. It was found that while PATUH has managed to reduce the amount of cases of illegal occupation of state land, it did not do well in recovering revenues to the state. This study proposes that land charges under PATUH should be increased if revenue to the state is to be significantly improved.